Room Temperature Surface Bio-Sulfurisation via Natural Sativum Annilin and Bioengineering of Nanostructured CuS/Cu2S - Welegergs, G. G.; Numan, N.; Dube, S.; Nuru, Z; Botha, N; Azizi, S.; Cloete, K; Akbari, M; Morad, R; Tsegay, M. G.; Gebretinsae, H.G.; Mtshali, C.; et al. (Nano-Horizons: Journal of Nanosciences and Nanotechnologies)
In this contribution, we report, for the first time, on the surface bio-sulfurisation of metallic surfaces at room temperature via natural sativum annilin. More precisely, this bio-sulfurisation is validated on bioengineered nanostructured Cu2-XS surfaces using natural organosulfur compounds emitted from Sativum allium L. as efficient sulfurisation chemical agents. It is validated that virgin copper surfaces can be sulfurised at room temperature without adding any extra chemical or physical processes. In addition to the validation of the green sulfurisation process of the copper surface, the bioengineered Cu2-XS exhibited a multiscale 1-D tubular morphology with Cu2-XS nanotubules and nanocones. Such a nanostructured Cu2-XS surface exhibited an excessive optical selectivity, a superhydrophobicity response in addition to a remarkable site selective mercury adsorption.